2001
DOI: 10.7589/0090-3558-37.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Fluorescence Polarization Assay and Comparison to Other Serological Assays for Detection of Brucellosis in Cervids

Abstract: The complement fixation test (CFT), competitive enzyme immunoassay (CELISA), indirect enzyme immunoassay (IELISA) and fluorescence polarization assay (FPA) were evaluated for the detection of antibodies to Brucella abortus and Brucella suis biotype 4 in caribou (Rangifer tarandus caribou), elk (Cervus elapus), red deer (Cervus elapus), and reindeer (Rangifer tarandus tarandus). When combining the data the FPA and the CELISA were determined to be the most suitable tests for serodiagnosis of Cervidae. The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 13 publications
3
33
2
Order By: Relevance
“…The C-ELISA, I-ELISA, and FPA perform well with regards to sensitivity and specificity in sera from wild species whereas the BPAT performed relatively poorly (Gall et al, 2001). Therefore, it is assumed that the BPAT test overestimated the number of positive HMSs in this survey.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The C-ELISA, I-ELISA, and FPA perform well with regards to sensitivity and specificity in sera from wild species whereas the BPAT performed relatively poorly (Gall et al, 2001). Therefore, it is assumed that the BPAT test overestimated the number of positive HMSs in this survey.…”
Section: Discussionmentioning
confidence: 88%
“…As with other wild species, the FPA test is the diagnostic test of choice for detection of exposure to Brucella in HMSs (Gall et al, 2001). It has the ability, in some cas-es, to distinguish antibody from cross-reacting organisms (e.g., Y. enterocolitica 0:9) from antibody against Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently described the use of FP assays, using a fluorescein-labeled OPS from Brucella abortus, for the detection of antibodies to Brucella spp. (a gram negative bacterium) in bovids, bison, cervids and swine [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. We have shown that this approach, in principle, can be applied to all gram negative bacteria, which possess OPSs, by extending it to the detection of antibodies to Salmonella spp.…”
Section: Introductionmentioning
confidence: 88%
“…The assay was evaluated against a variety of commonly used assays (the buffered plate antigen test, the rose bengal plate test, the complement fixation test, the rivanol agglutination test, competitive ELISA, indirect ELISA and culture) in bovine sera [6,[10][11][12][19][20], porcine sera [13][14], bison sera [15], cervid sera [16], bovine whole blood [8,17,19], and bovine milk [8,18,19,21]. In all these studies the FPA was equal, and many times superior to the commonly used assays in terms of sensitivity and specificity, often achieving 99+% for both.…”
Section: The Fpa For the Detection Of Brucella Spp In Animal Body Flmentioning
confidence: 99%